The Effect of Combination Health Education: Snake Ladder Game and Sing- a-Song Methods to Improve Personal Hygiene Behavior in School-Age Children - Kurnia, Iqlima Dwi; Kurniawati, Lailaturohmah; Has, Eka Misbahatul M. (International Journal of Psychosocial Rehabilitation, 2020)
Primary school-age children are the group of age prone to many kinds of diseases caused by poor personal hygiene. Most of the students who suffer from infectious diseases are caused by the lack of personal hygiene. One way to improve their behavior is by using health education. The purpose of this study was to analyze the effect of combination health education: snake ladder game and sing a song toward improving personal hygiene behavior in primary school-age children. This study design was quasi-experimental. The total number of respondents was 120 children. The respondents were recruited randomly based on G*Power. The independent variables in this study were combination of health education: snake ladder game and sing a song. The dependent variable was personal hygiene behavior. The instruments of the study were a ladder snake board and singing completeness as well as a questionnaire for personal hygiene. The data were collected used questionnaires and observation then it was analyzed using significance of <0,05 Wilcoxon sign rank test, Mann- Whitney U test and the Kruskal–Wallis H test. The result showed there were significant effects of health education with snake ladder game and sing-a-song methods to respondents’ knowledge (p=0.000), attitudes (p=0.000) and action (p=0.000). The Kruskal–Wallis H test obtained the best mean value, knowledge of 86.65, attitude of 82.77, and skill of 89.87. Health education by using the Snake-and -Ladder Game and Sing-a-Song method could increase the behavior about personal hygiene for 7-10-year-old students in primary school. Nurses can apply this method to have an easier and more attractive way of giving health education and to achieve optimal results in the health education for children.